TYPES OF AFFECTIVE ASSESSMENT JENIS PENILAIAN AFEKTIF: JENIS PENILAIAN AFEKTIF - Mutmainah Latabi; Frezy Paputungan (LPPM UNiversitas Bina Mandiri Gorontalo, 2022)
It is well recognized that learning is influenced by four affective traits: (1) interests; (2) attitudes; (3) self-concept; and (4) values. Goals of affective assessment: 1) to determine students' attitudes toward accounting subjects; the results of attitude measurement are useful for determining appropriate learning strategies for students; 2) to determine students' interest in accounting subjects, which is then used to increase it if it turns out that students' interest is low. 3) to identify their own strengths and weaknesses, as well as the programs that students should enroll in to determine their career paths. 4) To reveal personal values; the information is obtained in the form of positive and negative values, with the positives being emphasized and the negatives being minimized